RP-HPLC Analysis of Trandolapril in Pharmaceutical Dosage Forms - KUMAR LAHA, TAPAS; ADHIKARI, LOPAMUDRA; SANNIGRAHI, SANTANU; SEN, SUBRATA (Asian Journal of Chemistry, 2010)
A rapid and sensitive reverse phase HPLC method is applied for the qualitative and quantitative assay of trandolapril in pharmaceutical dosage forms. Trandolapril was chromatographed on a reverse phase C18 column with a mobile phase consisting of methanol:phosphate buffer (pH 7.8) in the ratio of 90:10 v/v. The mobile phase was pumped at a flow rate of 1 mL/min. Mizolastine was used as an internal standard and the eluents were monitored at 220 nm. The retention time of the drug was 2.634 min. With this method, linearity is observed between area under curve (AUC, expressed in mV.min) and concentration of trandolapril in the injected solution, in the range of 5-150 μg/mL. The method was found to be applicable for analysis of drug in tablets. The results of the analysis were validated statistically.